Evidence that nitric oxide mechanisms regulate small intestinal motility in humans. Issue 1 (1st January 1999) - Russo, A; Fraser, R; Adachi, K; Horowitz, M; Boeckxstaens, G
Abstract : Background: Non-cholinergic non-adrenergic neural mechanisms involving nerves containing NO have been shown to modulate smooth muscle in the gastrointestinal tract, and it has been suggested that release from tonic NO inhibition may be important in the regulation of cyclical fasting small intestinal motility. Aims: To evaluate the role of NO mechanisms in the regulation of fasting small intestinal motor activity in humans using a specific NO synthase inhibitor, N G -monomethyl-l -arginine ( l -NMMA). Methods: In seven healthy male volunteers, duodenal and jejunal pressures were measured for four hours with a nine lumen manometric catheter. Volunteers attended on four separate days on which they received an intravenous infusion of either saline or l -NMMA (0.5, 2, or 4 mg/kg/h) in random order. Intravenous infusions began 10 minutes after completion of phase III of the migrating motor complex (MMC). Results: The first episode of phase III activity occurred earlier after infusion of 2 and 4 mg/kg/h l -NMMA than after infusion of 0.5 mg/kg/hl -NMMA or saline (mean (95% confidence interval) 52 (36–68) and 57 (18–97) v 116 (69–193) and 145 (64–226) minutes respectively) with a resultant MMC cycle length of 82 (59–105) and 86 (46–126) v 132 (49–198) and 169 (98–240) minutes respectively. The total number of phase III activities during the four hour recording was increased (p<0.05) by l -NMMA at a dose of 4 mg/kg/h (2 (1–3)) but not at 2 mg/kg/h (1.5 (1–2)) or 0.5 mg/kg/h (1.3 (1–2)) compared with saline (1.3 (0.6–2)). l -NMMA had no effect on the duration, velocity, number of contractions per minute, length of migration, or site of origin of phase III of the MMC. The duration of phase I activity was shorter (p<0.05) with 4 mg/kg/hl -NMMA than with saline (12 (1–23) v 31 (19–44) minutes). Conclusions: These observations suggest that NO mechanisms play a role in the regulation of fasting small intestinal motor activity in humans.